ANALISIS LAGU PETANG LAH PETANG - Deta Liandra; Jagar L. Toruan; Yensharti Yensharti (FBS Universitas Negeri Padang, 2016)
This article is aimed at analyzing the song Petang Lah Petang based on the song structure and melody composition. This is a qualitative research that uses the conten analysis approach. The theory used to analyze the song is the melodic structure, melodic composition and song structure theory. Data collection was done through recording, library research and laboratory work ( analysis process). The result of the analysis shows that the song Petang Lah Petang belongs to the category of song which have two musical phrases of AB such as pharases a, a1 (antecedent) and b, b1, b2 (consequents). It was also found that the song has seven types of motives (m, n, o, m1, n1, o1,o2), the chords of the song consists of basic chord such as chords I, IV and V. it also as one type of cadence (perfect authentic cadence). The length of the phrases is different or also khown as contrasting phrase. The melodic formulation of the song consists of both disjunction and conjunction. Looking at the melodies and lyrics of the song, it can be concluded that Petang Lah Petang belongs to the group of songs called logogenic or songs whose lyrics dominate the melodies. In other words, this song is not perfect because it only emphasizes on the use of one type of form or also khow as syllabic song. Having analyzed the lyrics of this song and their link with the direction of melody, it is found that the song is a reflection of the tradition of ‘take and give’ – from the community, to the community. Some of the lyrics of the song contain orders and good advice (a reflection of life in the Lahat community) to be passed down to the next generation in the community.